Pengaturan Kewenangan, dan Tanggung Jawab Direksi Dalam Perseroan Terbatas (Studi Perbandingan Indonesia dan Australia) - Kusumawardani, Shinta Ikayani (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 1 (2013), 2013)
Research on: The Rules Regarding  The Powers and Responsibilities Of Directors In A Limited Liability Company (Comparative Study of Indonesia and Australia) . As for the issues discussed in this study related to the application of the authority of the board of directors in the management of a limited liability company under the principle of fiduciary duty Australia comparison of Indonesia can not be separated from the authority granted will cause responsibility that must be borne by the company’s board of directors in managing and also the characteristics of the type of responsibility of Directors This study uses normative juridical approach. Juridical Approaches to run whether the provisions of law relating to kewenagan concrete and responsibilities of the Board of Directors in the management Company Limited Comparative Study of Indonesia and Australia, while Normative is the cover of the principles of law, comparative law, the elements and factors related to authority and responsibility of the Company's Board of Directors in the management of one heart-to-day. This study on Duties and Responsibilities of Directors is normative legal research that emphasizes the study of literature. The purpose of this research is to know the duties and responsibilities of the Board of Directors of Limited Liability Company under the law. Data analysis was performed using the comparative method of qualitative. From the results of this analysis are expected to obtain an accurate picture and understanding of the duties and responsibilities of the Board of Directors of Limited Liability Company. To this effect, a comparison of the authority and responsibilities of the Board of Directors in the management of the Company as the Company's assessment of body organ is the comparison between the authority of the Board of Directors in Indonesia and in Australia the comparative results indicate that the system of regulation in Indonesia and Australia are more inclined to use the model and not a model enabling mandatory because it is based by the condition of the structure of capital ownership. Fiduciary obligations, particularly on legislation in both Indonesia and Australia appear as incomplete law and need to be interpreted by the fid uciary. The main essence of this comparison as the basis for further transplants Indonesia that fiduciary obligations may fruitfully dalamn Handling Company Limited.
Keywords: Authority and Responsibility of the Board of Directors; Company Limited